The Influence of Destination Brands on the Satisfaction and Revisit Intention of Foreign Tourists at the Agro-tourism of Ceking Rice Field Terrace in Bali - Wicaksana, I Putu Wahyu; Suryawardani, I G A Oka; Dewi, Ratna Komala (E-Journal of Tourism, 2020)
Agrotourism attraction of Ceking Rice Field Terrace Village is a natural panorama of rice fields terrace has been recognized as heritage that should be preserved. The purpose of this study is to find out the influence of destination brands on the interest of foreign tourists in Ceking Rice Field Terrace Agrotourism and the obstacles faced in building destination brands in Ceking Rice Field Terrace tourist destinations. The independent variables of this research are part of the brand destination, namely brand awareness, brand image and brand association. The dependent variables are customer satisfaction and revisit intention. Research was design based on structural equation model. Data was analyzed by using Smart-PLS version 3.0. Brand awareness, brand image and brand association had a significant and positive influence on the satisfaction of foreign tourists and their revisit intention. The results also showed that the constraints faced by Agrotourism Rice Field Terrace in building a destination brand area, the name of Agrotourism Ceking Rice Field Terrace has not been known as a name of attractive tourist destination and the lack of handicrafts that have the characteristics of the Agrotourism. Keywords: agrotourism, brand destination, and revisit intention